Synthesis and polymerization of vinylcyclopropanes bearing urethane groups for the development of low-shrinkage composites. (January 2018) - Catel, Yohann; Fässler, Pascal; Fischer, Urs; Gorsche, Christian; Liska, Robert; Schörpf, Sebastian; Tauscher, Sven; Moszner, Norbert
Graphical abstract: Highlights: Synthesis of seven vinylcyclopropanes bearing urethane groups. Determination of polymerization rates using Photo-DSC. Evaluation of the rheological behavior using real time-NIR-photorheology. Formulation and characterization of innovative low-shrinkage dental composites. Influence of the urethane group on the mechanical properties of the tested composites. Abstract: Polymerization shrinkage of methacrylate-based dental composites remains a major concern in restorative dentistry. Cyclic monomers, such as 1, 1-disubstituted 2-vinylcyclopropanes, might represent an interesting alternative to dimethacrylates in order to reduce shrinkage. In this contribution, the synthesis of seven crosslinking vinylcyclopropanes bearing urethane groups is described. These monomers were synthesized by esterification of 1-ethoxycarbonyl-2-vinylcyclopropane-1-carboxylic acid with either ethylene glycol or diethylene glycol, followed by a reaction with selected diisocyanates. In order to evaluate the reactivity of the synthesized vinylcyclopropanes, their photopolymerization behavior was investigated by photo-differential scanning calorimetry. Real-time (RT)-NIR-photorheology measurements were performed to evaluate rheological behavior (i.e. time of gelation, polymerization induced shrinkage force) and chemical conversion (i.e. double bond conversion at the gel point, final double bond conversion) of the vinylcyclopropanes in situ . Composites based on these monomers show good to excellent mechanical properties and exhibit low shrinkage. The presence of urethane groups provides a significant improvement of the mechanical properties. The replacement of methacrylates by urethane vinylcyclopropanes appears to be a promising approach to develop low-shrinkage dental composites without sacrificing the mechanical properties.